2008
DOI: 10.1016/j.jrp.2007.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The good judge of personality: Characteristics, behaviors, and observer accuracy

Abstract: Personality characteristics and behaviors related to judgmental accuracy following unstructured interactions among previously unacquainted triads were examined. Judgmental accuracy was related to social skill, agreeableness, and adjustment. Accuracy of observers of the interactions was positively related to the number of good judges in the interaction, which implies that the personality and behaviors of the judge are important for creating a situation in which targets will reveal relevant personality cues. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
124
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 37 publications
5
124
0
Order By: Relevance
“…personality judgment | social media | computational social science | artificial intelligence | big data P erceiving and judging other people's personality traits is an essential component of social living (1,2). People use personality judgments to make day-to-day decisions and long-term plans in their personal and professional lives, such as whom to befriend, marry, trust, hire, or elect as president (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…personality judgment | social media | computational social science | artificial intelligence | big data P erceiving and judging other people's personality traits is an essential component of social living (1,2). People use personality judgments to make day-to-day decisions and long-term plans in their personal and professional lives, such as whom to befriend, marry, trust, hire, or elect as president (3).…”
mentioning
confidence: 99%
“…People use personality judgments to make day-to-day decisions and long-term plans in their personal and professional lives, such as whom to befriend, marry, trust, hire, or elect as president (3). The more accurate the judgment, the better the decision (2,4,5). Previous research has shown that people are fairly good at judging each other's personalities (6)(7)(8); for example, even complete strangers can make valid personality judgments after watching a short video presenting a sample of behavior (9,10).…”
mentioning
confidence: 99%
“…Although some subtle individual differences in the ability to judge others' personality have been observed, no large between-individual differences have been discovered in the judgment of personality traits (Bayne, 1985;Christiansen, Wolcott-Burnam, Janovics, Burns, & Quirk, 2005;Ickes, Buysse, et al, 2000;Letzring, 2008;McLarney-Vesotski, Bernieri, & Rempala, 2011;Taft, 1955). There are, of course, individual differences in empathic accuracy -another name for self-other agreement -but they do not seem to be either large or systematic (Davis & Kraus, 1997;Ickes, 1997).…”
mentioning
confidence: 99%
“…Zaki and Ochsner relate the history of the search for the "good judge" in the traditional fashion. Although plenty of interesting findings about the good judge can be found in the contemporary literature (see Letzring, 2008), the nature of some of the historically long-standing problems in that area of research illustrate the value of the points raised by the target article. One reason why the search for the good judge has proven so difficult is that properties of the judge, target, trait, and information on which the judgment is based all might interact in the determination of accuracy.…”
Section: Rammentioning
confidence: 99%